Efikasi Ekstrak Daun Sirih Terhadap Alternaria porri Penyebab Penyakit Bercak Ungu Pada Bawang Merah Secara In vitro - Muh. Fahrun; Johanis Panggeso; Rosmini Rosmini (Fakultas Pertanian, Universitas Tadulako, 2018)
Purple spot caused by the fungus A. porri is an important disease that attacks the shallot crop and causing several production centers in Indonesia. Purple spot disease control still use chemical fungicides so it is necessary to control alternative vegetable fungicides. One is the betel leaf vegetable fungicides. Betel leaf have anti fungus characteristic, and anti-oxidants with essential oil component is eugenol 63.39%, 14.05% acetyleugenol. The purpose of this research to determine the effectiveness of betel leaf extract in inhibiting the growth of disease-causing fungus A. porri purple spots on shallots. Implementation of research at the Laboratory of Plant Pests and Diseases (HPT) Faculty of Agriculture, University Tadulako, Central Sulawesi. Palu. The research began in January to September 2016. The test method respectively betel leaf extract concentration in 2 ml pour into PDA medium. Once solidified, A. porri ose taken using a needle and placed right in the middle. The results showed that the betel leaf extract effectively inhibits the growth of A. porri, the highest concentration in inhibiting A. porri growth is 8%. The result of regression analysis of betel leaf extract concentration toward percentage of inhibition A. porri showed very strong correlation relationship (0,904).